2011
DOI: 10.2527/jas.2011-4014
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation kinetics and postthaw motility of flow cytometric-sorted white-tailed deer sperm1

Abstract: This study examined DNA damage and postthaw motility of white-tailed deer sperm (n = 28) before and after sex selection and conventional sorting using MoFlo XDP SX flow cytometry. Semen samples from the same individuals were treated in 4 different ways: 1) chilled-extended sperm samples (without glycerol); 2) cryopreserved conventional samples, samples directly cryopreserved after the addition of extenders; 3) cryopreserved conventionally sorted samples, sorted samples to remove the dead sperm subpopulation; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…One of them is the sex selection of sperm to determine the gender of the offspring with over 90% accuracy. Studies have shown that sex sorting does not affect the quality of DNA on species like deer [61] and boar [62]. However, its effect is still to be determined on bovine sperm since studies have shown that, although DNA fragmentation right after thawing is higher in conventional than in sex-sorted sperm samples, a reduced DNA longevity in sex-sorted spermatozoa was detected when the samples were incubated for 48 h [63].…”
Section: Causes Of Dna Fragmentationmentioning
confidence: 99%
“…One of them is the sex selection of sperm to determine the gender of the offspring with over 90% accuracy. Studies have shown that sex sorting does not affect the quality of DNA on species like deer [61] and boar [62]. However, its effect is still to be determined on bovine sperm since studies have shown that, although DNA fragmentation right after thawing is higher in conventional than in sex-sorted sperm samples, a reduced DNA longevity in sex-sorted spermatozoa was detected when the samples were incubated for 48 h [63].…”
Section: Causes Of Dna Fragmentationmentioning
confidence: 99%
“…With regard to the present study, it was hypothesized that in shellfish, as in mammals (Kjelland, González‐Marín, Gosálvez, López‐Fernández, Lenz, Evans & Moreno ), fish (López‐Fernández et al . ; Gosálvez, López‐Fernández, Hermoso, Fernández & Kjelland ) and reptiles (Johnston, López‐Fernández, Arroyo, Fernández & Gosálvez ), the semen holds a in every ejaculate holds a certain proportion of sperm that does not meet the minimal requirements for fertilization.…”
Section: Introductionmentioning
confidence: 94%
“…In the present study, a sample of 15 × 10 6 sperm/mL was diluted in agarose to give a final concentration of 1 × 10 6 sperm/mL, placed in racks, lysed, and stained with DAPI (SIGMA, 4'-6-diamidino Obtained 2-phenylindole) and Wright stain (Accustain, Sigma) to obtain two slides for each epididymal segment sample. Kjelland et al [28] provides a more detailed sperm sample preparation protocol using the Halomax kit (Figure 1). The DNA fragmentation analyses were conducted using a fluorescence microscope (FV10i, OYMPUS) using a magnification of 1000X with the DAPI stain, but without filters for the WRIGHT stain.…”
Section: Evaluation Of Sperm Dna Integritymentioning
confidence: 99%